ISLAMIC FINTECH LENDING DETERMINANTS USING ISLAMIC FINANCIAL LITERACY AS A MODERATION VARIABLE - Mahmud, Muhammad Daud Bin; Quilim, Cici Aryansi; Salmatia, Salmatia (Finansha: Journal of Sharia Financial Management, 2024)
This study aims to determine the financial literacy of MSME actors in Morotai Island Regency as well as their erceptions in utilizing islamic fintech lending as an alternative business funding. Moderated Regression Analysis (MRA) with SPSS version 25 is the analysis approach used. 108 MSME units in six randomly chosen sub-districts received questionnaires with slovin technique, which was applied with a 0.05 margin of error and predetermined criteria. The study's findings demonstrate that the usage of islamic fintech lending is highly influenced by the perceived usefulness and ease of use of fintech. In addition, this study discovered that the impact of perceived usefulness and perceived ease of use on the frequency with which MSMEs use islamic fintech lending is not moderated by islamic financial literacy. The study's practical contribution is the realization that islamic financial literacy apart cannot be as a criteria for evaluating how MSME utilize islamic fintech lending to obtain funding for company expansion. Further research is necessary on digital literacy, which refers to MSME actors' ability in utilizing technology and digital platforms to obtain fintech funding. In addition, it's essential to focus on external factors like the availability of Islamic financial technology funding education and training for MSME.